2019
DOI: 10.5194/isprs-archives-xlii-4-w18-949-2019
|View full text |Cite
|
Sign up to set email alerts
|

Proposing a New Method for Encrypting Satellite Images Based on Hash Function and Chaos Parameters

Abstract: Abstract. Due to the importance of providing security in satellite imagery and their transmission, in this paper, a new method for encrypting satellite images based on Hash key-based symmetric cryptographic algorithm is proposed which is developed by combining the generated key and chaos mapping parameters. The benefits of this algorithm are high security, high sensitivity and using dynamic encryption blocks. The proposed algorithm consists of three main parts: in the first section, the encryption key is creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The information entropy for numerous encrypted images was computed in this paper, and the results, as outlined in table 5, demonstrate that the entropies of all encrypted images closely approximate 8. Therefore, it can be concluded that our scheme has an average entropy of 7.9997 and is superior to the schemes in [28][29][30][31][32].…”
Section: Information Entropy Analysismentioning
confidence: 79%
“…The information entropy for numerous encrypted images was computed in this paper, and the results, as outlined in table 5, demonstrate that the entropies of all encrypted images closely approximate 8. Therefore, it can be concluded that our scheme has an average entropy of 7.9997 and is superior to the schemes in [28][29][30][31][32].…”
Section: Information Entropy Analysismentioning
confidence: 79%
“…Among them, the highest information entropy is 7.9994. Besides, compared with other similar remote sensing image encryption algorithms [58,59], the results show that the proposed algorithm has higher information entropy.…”
Section: Information Entropy Analysis Information Entropy Proposed By Shannonmentioning
confidence: 96%